The Shelf-life, Microbiology Quality, and Characteristic Changes of Probiotic Lactobacillus plantarum Dad-13 Milk Jelly Candy during Storage - Rafli Zulfa Kamil; Fida Hasna Fadhila; Angela Dea; Endang Sutriswati Rahayu; Subekti Hartiningsih (The University of Lampung, 2023)
Probiotics are live microorganisms that, when consumed in sufficient amounts, can provide health benefits to their host. L. plantarum Dad-13 milk jelly candies are non-fermented probiotic products. This study aims to evaluate the changes in the characteristics of probiotic milk jelly candies during storage and their microbiological quality. Characteristics such as pH, water activity (aw), hardness, chewiness, gumminess, brightness, and viability of lactic acid bacteria were analyzed over a period of 4 weeks at two temperatures, namely 4 and 30°C. Sub-lethal injury analysis was conducted to estimate the survival of probiotic cells during the jelly candy manufacturing process. Microbiological quality was assessed through Total Plate Count (TPC), Coliform, Escherichia coli, Salmonella, Mold, and Yeast analyses. The research results showed that the number of probiotic cells experiencing injury was less than 5%. Furthermore, changes in physical characteristics were observed during the 4-week storage period, but the temperature difference only affected pH and aw. The viability of lactic acid bacteria was more stable at a storage temperature of 4°C, and the microbiological quality met the jelly candy standards, except for TPC. Based on the research findings, milk jelly candies can be used as a carrier for probiotic cells as a non-fermented probiotic product innovation, with a recommended storage temperature of 4°C and best consumed within 47 days. Additionally, probiotic milk jelly candies are free from other microbial contamination. Keywords: Jelly candy, L. plantarum Dad-13, Microbiological quality, Probiotic, Storage